Monoclonal antibody therapy for refractory chronic migraine-like headache related Lyme disease: a case report - Cantillo-Martínez, Marlon; Correa-Arrieta, Cristian; Sobrino-Mejía, Fidel (Headache Medicine, 2024)
Introduction Lyme disease, caused by Borrelia burgdorferi, can lead to diverse neurological manifestations, including headache. While most Lyme-associated headaches resolve with antibiotics, some may evolve into a refractory chronic migraine-like syndrome. We present a case of post-Lyme chronic migraine-like headache responsive to galcanezumab, a calcitonin gene-related peptide (CGRP) monoclonal antibody. Case Report A 42-year-old woman developed chronic migraine-like headaches following treatment for Lyme neuroborreliosis. The headaches were refractory to standard preventive therapies and only partially responsive to onabotulinumtoxinA. Administration of galcanezumab resulted in significant reduction of headache frequency, intensity, and impact on daily activities. Comment This case highlights the potential of CGRP-targeted therapies for persistent migraine-like headaches following Lyme neuroborreliosis. The favorable response to galcanezumab suggests a role for CGRP in the pathophysiology of post-Lyme headache. While further research is needed to establish efficacy and safety, clinicians should consider CGRP monoclonal antibodies for chronic migraine-like headaches refractory to standard treatments in the post-infectious phase of Lyme disease. The emergence of chronic migraine-like headaches following Lyme neuroborreliosis and the response to a CGRP monoclonal antibody in this case underscore the importance of considering targeted migraine therapies in the management of persistent headaches after antibiotic treatment. This report contributes to the understanding of Lyme disease sequelae and potential treatment options, warranting further investigation into the utility of CGRP-targeted therapies in this context.